Digital Marketing Ethics 5.0: An Analysis of Islamic Economics - Hardiansyah Padli (BALQIS : Journal of Business Innovation and Digital Marketing, 2025)
The development of the marketing landscape in the era of Marketing 5.0 is marked by the integration of advanced technologies such as artificial intelligence (AI), big data, and machine learning, which enable greater personalization and more intensive interaction with consumers. However, these advances present significant ethical challenges, including data privacy violations, greenwashing practices in sustainability claims, and potentially discriminatory algorithmic bias. These problems erode consumer trust, which is the main foundation of the digital marketing ecosystem. This study aims to analyze these issues from an Islamic economic perspective, emphasizing normative values as the basis for ethics. The method used is a conceptual analysis based on a literature review, examining literature on digital ethics in Marketing 5.0 and the basic principles of Islamic economics, such as tauhid, al-'adl, an-nubuwah, al-khilafah, and al-ma'ad. The results of the analysis show that privacy can be understood within the framework of tauhid as respect for human dignity, greenwashing can be criticized through the principles of honesty and prophetic trust, while algorithmic bias can be addressed with the principles of justice ('adl) and khailifah responsibility. Thus, the normative framework of Islamic economics is not only capable of providing ethical solutions to digital marketing issues, but also presents an alternative paradigm that emphasizes a balance between profitability, social justice, and sustainability. This study concludes that the integration of Islamic values in Marketing 5.0 is a new conceptual contribution that strengthens the literature on sustainable marketing while paving the way for the development of a theory of marketing based on transcendental ethics.